m+73/3=26

Simple and best practice solution for m+73/3=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+73/3=26 equation:



m+73/3=26
We move all terms to the left:
m+73/3-(26)=0
determiningTheFunctionDomain m-26+73/3=0
We multiply all the terms by the denominator
m*3+73-26*3=0
We add all the numbers together, and all the variables
m*3-5=0
Wy multiply elements
3m-5=0
We move all terms containing m to the left, all other terms to the right
3m=5
m=5/3
m=1+2/3

See similar equations:

| 5y-17=2y-25 | | -6=2(r-65) | | -6=2(r+ | | 8(h+-18)=-56 | | 5y+17=2y-23 | | 292=239-x | | 8(h+(-18))=-56 | | 1/4(x-7)=1+3× | | 4x-12=2x-9 | | 3=h/7-2 | | -8(y-1.25=4 | | 3=d/26-1 | | 3x-49+2x=x+31 | | 3÷2y=12 | | 21=5-4d | | 7(d-75)=91 | | 3b=12-b | | -46+2d=30 | | 0=g-100/(-5) | | 4(s+44)=-8 | | -7x+8(8+5x)=25 | | 0.15=x*120 | | 71=y+5 | | 10=r+11/3 | | j/4+8=-2 | | 3(2x-4)=2(2x+2)+2x | | 3z+12=99 | | 6(x-5)=3 | | 2(-9x+3)=3x+9 | | 6x-12=4x+4+2x | | 3n2127n+1386=0 | | 21-x=171-6x/9 |

Equations solver categories